A147 ENDOSCOPIST FEEDBACK IS ASSOCIATED WITH IMPROVEMENTS IN COLONOSCOPY QUALITY INDICATORS: A SYSTEMATIC REVIEW AND META-ANALYSIS. (26th February 2020) - Bishay, K; Calo, N; Scaffidi, M A; Walsh, C M; Anderson, J; Rostom, A; Dube, C; Keswani, R N; Heitman, S; Hilsden, R J; Shorr, R; Grover, S C; et al.
Abstract: Background: Colonoscopy quality indicators such as adenoma detection rate (ADR) are surrogates for the effectiveness of screening-related colonoscopy. Endosocpist feedback may be associated with improvements in ADR and other quality indicators. Aims: To conduct a systematic review and meta-analysis to determine whether an association exists between endoscopist feedback and improvements in colonoscopy quality indicators. Methods: An electronic and manual search was conducted through May 2019 for studies reporting on endoscopist feedback and associations with ADR or other colonoscopy quality indicators. Studies primarily assessing the effect of audit and feedback on trainees and studies that included interventions other then feedback were excluded from the analysis. Pooled rate ratios (RR) and weighted mean differences (WMD) were calculated using DerSimonian and Laird random effects models. Subgroup, sensitivity and meta-regression analyses were performed to assess for potential methodological or clinical factors associated with outcomes. Results: Of 1, 326 initial studies, 12 studies were included in the meta-analysis for ADR, representing 33, 184 colonoscopies. Endoscopist feedback was associated with an improvement in ADR (RR 1.21, 95% confidence interval, CI, 1.09 to 1.34). Low performers derived a greater benefit from feedback (RR 1.62, 95% CI 1.18 to 2.23) compared to moderate performers (RR 1.19, 95% CI 1.11 to 1.29), while high performers did not derive a significant benefit (RR 1.06, 95% CI 0.99 to 1.13). Feedback was not associated with increases in withdrawal time (WMD +0.43 minutes, 95% CI -0.50 to +1.36 minutes) or improvements in cecal intubation rate (RR 1.00, 95% CI 0.99 to 1.01). Conclusions: Endoscopist feedback is associated with modest improvements in ADR. Routine audit and feedback may be a feasible strategy to optimize outcomes in screening colonoscopy. Funding Agencies: None